Twitter Style: An Analysis of How House Candidates Used Twitter in Their 2012 Campaigns - Evans, Heather K.; Cordova, Victoria; Sipole, Savannah (PS, political science & politics, 2014)
This article examines how House candidates used Twitter during the 2012 campaign. Using a content analysis of every tweet from each candidate for the House in the final two months before the 2012 election, this study provides a snapshot of House candidates’ “Twitter style.” In particular, this article shows that incumbents, Democrats, women, and those in competitive races tweet differently than challengers, Republicans, minor party candidates, men, and those in safe districts.